2014
DOI: 10.1016/j.geb.2014.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Robustness to strategic uncertainty

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 33 publications
(45 reference statements)
0
36
0
Order By: Relevance
“…Decisions under strategic uncertainty has been studied both experimentally (Abbink and Brands, 2008;Feltowich and Swierzbinski, 2011;Andersson et al, 2018) and theoretically (Andersson et al, 2014, Yamashita, 2015. Some works, including Abbink and Brandts (2005) studied the behavior under structural uncertainty, although most of the literature focused on pure effects of the varying market structures (Plott, 1995, Camerer, 2003and Huck et al 2004…”
Section: Related Literaturementioning
confidence: 99%
“…Decisions under strategic uncertainty has been studied both experimentally (Abbink and Brands, 2008;Feltowich and Swierzbinski, 2011;Andersson et al, 2018) and theoretically (Andersson et al, 2014, Yamashita, 2015. Some works, including Abbink and Brandts (2005) studied the behavior under structural uncertainty, although most of the literature focused on pure effects of the varying market structures (Plott, 1995, Camerer, 2003and Huck et al 2004…”
Section: Related Literaturementioning
confidence: 99%
“…Let G = (N, S, π) be an n-player normal-form game in which the strategy set of each player i ∈ N = {1, ..., n} is S i = R. Thus, S = R n is the set of strategy profiles, s = (s 1 , ..., s n ), and π : S → R n is the combined payoff function, with π i (s) being the payoff to player i when s is played. 2 We assume each payoff function π i to be Borel measurable and bounded but do not require continuity. Let F be the set of continuous and everywhere positive probability density functions on R. For φ ∈ F and any x ∈ R, let…”
Section: Robustness To Strategic Uncertaintymentioning
confidence: 99%
“…Although recentlyAndersson et al (2014) have studied an alternative refinement of the equilibrium set in price games, based on strategic uncertainty, and have shown that it selects prices different from the coalition-proof equilibrium. 14 Coalition-proofness has been applied to a wide range of different games, including cooperative games, as inHabis and Herings (2011).15 In defining coalition-proof equilibrium at the ex ante stage, one would have to take into account the possibility that sellers could share their private information as inWilson (1978).…”
mentioning
confidence: 99%